The sum of three consecutive even integers is 36. Let x represent the first integer, x + 2 represent the second integer, and x +
4 represent the third integer.
Which equation can be used to find the first integer?
3x = 2x + 6
2x + 6 = 36
3x + 6 = 36
3x + 36 = 2x + 6
2 answers:
Answer:
C. ![3x+6=36](https://tex.z-dn.net/?f=3x%2B6%3D36)
Step-by-step explanation:
Let x represent the first integer,
represent the second integer, and
represent the third integer.
The sum of these integers would be
.
We have been given that the sum of three consecutive even integers is 36. We can represent this information in an equation as:
![x+x+2+x+4=36](https://tex.z-dn.net/?f=x%2Bx%2B2%2Bx%2B4%3D36)
Combine like terms:
![3x+6=36](https://tex.z-dn.net/?f=3x%2B6%3D36)
Therefore, the equation
can be used find the first integer.
To start this, try to place it all together.
(x)+(x+2)+(x+4)=36
Then you start to combine so that it looks like this:
3x+6=36
I believe that is one of the choices. Do you need more explanation?
You might be interested in
Answer:
131.95yd squared
Step-by-step explanation:
A=2πrh+ 2 r(2)=2*π*3*4+2*π*3(2)~131.94689yd(2)
Answer:
B. Polygon ABCD was reflected over the x-axis and then reflected over the y-axis.
Answer:
73.75
Step-by-step explanation:
Answer:
P / 30 - 21= 9
2w = 9
w = 4.5
This should be the answer
Answer:
b+3a
Step-by-step explanation:
MN=AN+AM
AN=0.5*AB
AB=OA+OB=4a+2b
AN=2a+b
AM=OA-OM=4a-3a=a
MN=2a+b+a=3a+b